2013
DOI: 10.1007/s11999-012-2585-z
|View full text |Cite
|
Sign up to set email alerts
|

Is Posterior Synovial Plica Excision Necessary for Refractory Lateral Epicondylitis of the Elbow?

Abstract: Background Arthroscopic treatments for lateral epicondylitis including débridement of the extensor carpi radialis brevis (ECRB) origin (Baker technique) or resection of the radiocapitellar synovial plica reportedly improve symptoms. However the etiology of the disease and the role of the plica remain unclear. Results Two years postoperatively, we found no differences in the VAS pain score or DASH: the mean VAS pain scores were 0.3 points in Group A and 0.4 points in Group B, and the DASH scores were 5.1 points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Kim et al [ 2 ] reported arthroscopic results on 12 throwing athletes and attributed the plicae to this repetitive strain and trauma. Both Antuna and O’Driscoll [ 4 ] and Rhyou and Kim [ 11 ] described the pain caused by SP as a plausible differential diagnosis to lateral epicondylitis.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 2 ] reported arthroscopic results on 12 throwing athletes and attributed the plicae to this repetitive strain and trauma. Both Antuna and O’Driscoll [ 4 ] and Rhyou and Kim [ 11 ] described the pain caused by SP as a plausible differential diagnosis to lateral epicondylitis.…”
Section: Discussionmentioning
confidence: 99%
“…Debridement of the extensor carpi radialis brevis tendon 1) with synovial fold excision 4)12) 17) is the accepted treatment method for recalcitrant lateral epicondylitis. However, a recent report argues that the debridement of the extensor carpi radialis brevis tendon accompanied by posterior synovial fold excision does not provide any additional symptomatic improvement when compared with the debridement of only the extensor carpi radialis brevis tendon 18) . The relationship between lateral epicondylitis and synovial fold syndrome has not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Othman [22], in his study on 33 patients comparing the arthroscopic versus percutaneous release in treatment of chronic tennis elbow, noticed that the mean DASH score of the 14 patients who underwent arthroscopic release, improved from 72 points to 48 points postoperatively and he concluded that the arthroscopic treatment of lateral epicondylitis gives more favorable results in comparison to percutaneous one. Rhyou and Kim [23], in their retrospective study on 39 patients who underwent arthroscopic treatment for refractory lateral epicondylitis from November 2003 to October 2009. They grouped 20 patients treated with arthroscopic release of the ECRB origin.…”
Section: The Quick Dash Scorementioning
confidence: 99%